2017
DOI: 10.1016/j.trsl.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of the kidney in lupus nephritis to characterize response to treatment

Abstract: The consequences of treatment for the kidney at the molecular level have not been explored in human lupus nephritis (LN). In this investigation, changes in intra-renal transcript expression were measured and correlated with response in a LN cohort that underwent serial kidney biopsies. The intra-renal transcript expression of 19 patients with proliferative LN (Class III or IV) was measured at diagnostic biopsy (Bx1) and after induction therapy was completed (Bx2) using Nanostring® technology. Patients were seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…We hypothesized that local inflammatory conditions of LN are responsible for the discrepancy between CD163/CMAF positivity and HO-1 expression in glomerular Mϕ. In the present study, we focused on effects of IFN-α on mRNA expression of both molecules in human monocyte-derived M2-like Mϕ generated in vitro , because type I IFN and the related genes are upregulated in patients with LN, including the renal tissues as a so-called IFN signature [ 1 , 3 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that local inflammatory conditions of LN are responsible for the discrepancy between CD163/CMAF positivity and HO-1 expression in glomerular Mϕ. In the present study, we focused on effects of IFN-α on mRNA expression of both molecules in human monocyte-derived M2-like Mϕ generated in vitro , because type I IFN and the related genes are upregulated in patients with LN, including the renal tissues as a so-called IFN signature [ 1 , 3 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are needed to determine if early treatment with MMF in these patients may be beneficial to prevent TID. Novel approaches including molecular imaging, cell distance mapping, functional magnetic resonance imaging, as well as integrative biology approaches are being developed to identify early inflammatory changes, biomarkers and response to treatment in lupus nephritis [5255]. …”
Section: Discussionmentioning
confidence: 99%
“…In line with our own results, they reported that transcripts associated with leucocyte infiltration, T cell activation, complement pathway and interferon signature increased between baseline and follow-up in non-responders. 32 In the present study, we instead used an unbiased analytical approach, grouping the samples based on their molecular characteristics rather than predefined clinical categories, resulting in the identification of a link between T and B cell infiltration and activation, tubular damage and decreased renal function in LN. Tubulointerstitial lesions were previously already identified as a prognostic marker in LN.…”
Section: Discussionmentioning
confidence: 99%